PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE GROUP TO GROUP TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS IX SMPN 1 BAYANG KABUPATEN PESISIR SELATAN - Wahyuni, Suci; Rahmi, Rahmi; Pratiwi, Merina (STKIP PGRI Sumbar, 2013)
Background of this research based on studentsâ understanding of mathematical concepts was lack at grade IX SMPN 1 Bayang. This case was expected because of the learning process was centered on the teacher, students are not accustomed to discuss and construct knowledge during the learning process. One way to overcome this problem was implemented an active learning strategy Group To Group. This study aims to determine students understanding of mathematical concepts by applying active learning strategy Group To Group. Â Active learning strategy Group To Group was better than studentsâ understanding of mathematical concepts by applying conventional learning class IX students of SMPN 1 Bayang. This research was experimental research, with design of randomized trials on the subject. The population in this study was class IX SMPN 1 Bayang Academic Year 2013/2014. Sampling technique was randomly, one class be experimental class IX.2 and another class be control IX.4. The instrument of this research was final test with indicator concept understanding. The technique of data analysis was t-test formula with MINITAB. Based on data analysis was knownÂ both of classes are normally distributed and homogeneous samples and the result ofÂ hypothesis test used obtained P-value < Î±, so hypothesis research was accepted. Inconclusion students understanding of mathematical concepts by applying active learning strategy Group To Group was better than the students understanding of mathematical concepts by applying conventional learning class IX studentsâ of SMPN 1 Bayang in Academic Year 2013/2014.